The quality of life in inpatients i.e. patients with chronic schizophrenia - Mujabašič, Milada (Zdravniški vestnik, 2003)
Background. Whether in the prescription of appropriate types and doses of psychotropic medications or determining readiness for psychosocial treatment and rehabilitation, clinicians must be able to pinpoint, quantify, and monitorthes everity of psychiatric symptoms. Brief Psychiatric Rating Scale (BPRS) and LiSkal (Linzer Skala zur Messung der Lebensqualitaet bei Menschen mit chronischen psychosozialen Problemen) were proved to be reliable assessment tools and were used to quantify phenomenological features of schizophrenia in this study. Methods. 124 patients (76 male and 48 female) were interviewed in this study having the average age of 57. General information was taken from theircase histories andsymptoms were evaluated by means of the BPRS (Brief Psychiatric Rating Scale). In addition, LISKAL scale was used to evaluate quality of life and independence of patients. Data was processed and frequencies of categories for attribute variables as well as theaverage (xat) and standard deviation (SD) for numerical variables were calculated. Finally, 95% confidence limit was calculated. Results. Logistic regression model consisted of the following variables: living outside institutions in adulthood, working period, physical illness, motor slowing andbizzare delusions. The level of independence, measured with LiSkal scale, was 4 with both sexes. The evaluations of single sections in the questionnaireabout the quality of life ranged between 3 and 4. The evaluation of independence correlated with the complex evaluation of the life quality. Conclusions. Results showed that symptoms of illness (negatively) and general facts (positively) affected the quality of life of patients suffering from chronic schizophrenia.
Keywords: Brief Psychiatric Rating Scale; Institucionalizacija; Institutionalization; Kratka, psihiatrična ocena, lestvica; Kvaliteta življenja; Logistic Models; Logistični modeli; psihiatrija; psychiatry and clinical psychology; Psychology; Quality Of Life; Schizophrenia; Shizofrenija; simptomi